Indonesia in Halal Tourism: Overcoming Challenges to Stay on Top - Adriani, Isyana; Francoise, Jeanne (Parahyangan Center for International Studies, 2024)
This paper analyzes the background of Islamic tourism in Indonesia using the concept of Islamic tourism by Din (1989) and to analyze the development of halal tourism, it uses the halal concept by Liu et al. (2018). The paper looks at how the Indonesian government managed to enter the list of top ten global halal tourism destinations in 2018, got on top in 2019, only to slip several notches below due to the COVID-19 pandemic. It also looks at how, by involving non-state actors such as those in the fashion and culinary industries, Indonesia has managed to climb back on top in 2023. Last but least, the paper also gives recommendations on what the government should do to maintain Indonesia’s number one position in halal tourism. Keywords: Indonesia; halal tourism; Islamic heritage; travel; Muslim fashion